2014
DOI: 10.1002/2014gl061224
|View full text |Cite
|
Sign up to set email alerts
|

Long‐lived explosive volcanism on Mercury

Abstract: The duration and timing of volcanic activity on Mercury are key indicators of the thermal evolution of the planet and provide a valuable comparative example for other terrestrial bodies. The majority of effusive volcanism on Mercury appears to have occurred early in the planet's geological history (~4.1-3.55 Ga), but there is also evidence for explosive volcanism. Here we present evidence that explosive volcanism occurred from at least 3.9 Ga until less than a billion years ago and so was substantially more lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 46 publications
(71 reference statements)
0
63
0
Order By: Relevance
“…This peculiar distribution of the pyroclastic deposits may reflect their relatively young age [ Thomas et al , ] with respect to the effusive volcanism that fills the entire basin [ Ernst et al , ]. In fact, the subsurface structure of the Caloris basin should have many faults that penetrate deeper into the interior of Mercury at the edge of the basin [ Klimczak et al , ], thus favoring a deeper source for explosive volcanism, as often suggested for the Moon [ Gaddis et al , ].…”
Section: Mercury's Volcanismmentioning
confidence: 99%
“…This peculiar distribution of the pyroclastic deposits may reflect their relatively young age [ Thomas et al , ] with respect to the effusive volcanism that fills the entire basin [ Ernst et al , ]. In fact, the subsurface structure of the Caloris basin should have many faults that penetrate deeper into the interior of Mercury at the edge of the basin [ Klimczak et al , ], thus favoring a deeper source for explosive volcanism, as often suggested for the Moon [ Gaddis et al , ].…”
Section: Mercury's Volcanismmentioning
confidence: 99%
“…Portions of what have previously been termed intermediate plains (IPs) are also believed to be volcanically emplaced, though clear geomorphic evidence such as flow fronts has been mostly obliterated by intense cratering (e.g., Trask & Guest, 1975;Whitten et al, 2014). Geologically young pyroclastic deposits are found distributed across the globe, mostly within impact craters, though not necessarily associated with smooth plains (e.g., Goudge et al, 2014;Kerber et al, 2011;Thomas et al, 2014bThomas et al, , 2015.…”
Section: Introductionmentioning
confidence: 99%
“…The first hypothesis is consistent with the absence of spectral evidence for sulfide minerals in surface rocks (McClintock et al, 2008;Izenberg et al, 2014) while the second could explain the correlations between S and Ca-Mg observed in Mercurian lavas . Understanding the origin of high sulfur concentrations at the surface of Mercury is important to better constrain the structure of the planet and the distribution of sulfur amongst the different reservoirs (mantle, core and crust), the mechanisms of explosive volcanism (Kerber et al, 2009;Thomas et al, 2014a;Weider et al, 2016), and the formation of the hollows (sub-kilometer scale shallow depressions surrounded by bright deposits) which may have formed during sublimation of volatiles (Blewett et al, 2013;Thomas et al, 2014b).…”
Section: Introductionmentioning
confidence: 99%